2005
DOI: 10.1098/rspb.2005.3381
|View full text |Cite
|
Sign up to set email alerts
|

Ancient trans-Atlantic flight explains locust biogeography: molecular phylogenetics ofSchistocerca

Abstract: The desert locust (Schistocerca gregaria) has been an important agricultural pest at least since biblical times. Although the ecology, physiology and behaviour of this insect species have been well characterized, its biogeographical origins and evolutionary history are more obscure. Schistocerca gregaria occurs throughout Africa, the Middle East and Western Asia, but all other species in the genus Schistocerca are found in the New World. Because S. gregaria has the capacity for extreme long-distance movement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 35 publications
3
66
0
Order By: Relevance
“…Thus, the westward transatlantic flight from Africa to America is the only plausible explanation for the current distribution 57, 62, 64 . When the swarms of the desert locust crossed the Atlantic Ocean in 1988, they all perished without establishing any viable populations 62 , but it is not too far-fetched to imagine that such transatlantic dispersals could have happened in the past, and one of these events might have resulted in the original stock for the New World Schistocerca .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the westward transatlantic flight from Africa to America is the only plausible explanation for the current distribution 57, 62, 64 . When the swarms of the desert locust crossed the Atlantic Ocean in 1988, they all perished without establishing any viable populations 62 , but it is not too far-fetched to imagine that such transatlantic dispersals could have happened in the past, and one of these events might have resulted in the original stock for the New World Schistocerca .…”
Section: Discussionmentioning
confidence: 99%
“…Only two genera occur in the New World, Halmenus , a brachypterous genus endemic to the Galapagos Archipelagos 56 and Schistocerca , which shows an unusual transatlantic distribution. It has been previously suggested that Halmenus is actually a brachypterous member of Schistocerca 57, 58 . Within the genus, only the desert locust is found in the Old World (Africa and the Middle East) while all the other species occur in the New World (North, Central, and South America).…”
Section: Introductionmentioning
confidence: 99%
“…In their migratory stage, these insects can fly for days over several thousand kilometres in search of new habitats [1]. During this time their wings are subject to deformation, torsion and bending for millions of cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Kucharski et al 2008). Locust swarming and the expression of phase polyphenism appear to have arisen independently numerous times, which gives rise to two questions (Song 2005;Lovejoy et al 2006;Simpson & Sword 2009): (i) what is the role of genetics versus the environment in locust swarming and (ii) have unique mechanisms underlying the expression of phase polyphenism independently evolved several times, or are the differences among species due to modifications of the same gene regulatory pathways? Functional genomics resources for Locusta migratoria (Kang et al 2004;Ma et al 2006) offer tools for unravelling the molecular genetic mechanisms underlying locust phase change.…”
Section: Discussionmentioning
confidence: 99%